2020
DOI: 10.1177/0022487120971588
|View full text |Cite
|
Sign up to set email alerts
|

A Pretty Queer Thing: Thinking Queerly About Teachers’ Gender and Sexual Diversity–Focused Professional Learning

Abstract: Studying educators’ processes of learning to queer their practice has prompted us to think differently about our own praxis as teacher educators. Thinking differently has meant bringing the assumptions of queer theory and pedagogy to bear on our understanding of what is involved for teachers as they engage with difficult knowledge surrounding gender and sexual diversity in schools. In other words, it has meant organizing our approach to professional development around the assumption that learning, like pedagog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…For example, Smith and Payne (2016) found that educators’ attempts to integrate transgender students into schools reified the heteronormative structure, and Martino et al (2020) argued that school leaders use inclusive practices for individual transgender students to resist further structural changes to cisnormative systems. Staley and Leonardi (2020) propose the overarching approach to content learning needs to shift towards conversations of oppression, power, and the self with a greater focus on active learning that prepares teachers to “disrupt normativity.” Preparing teachers to disrupt normativity includes providing active learning opportunities. Rather than passively listening to a lecture on gender and sexuality in schools, active learning involves opportunities for reflection and to practice changing instruction, discipline, and social interactions.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Smith and Payne (2016) found that educators’ attempts to integrate transgender students into schools reified the heteronormative structure, and Martino et al (2020) argued that school leaders use inclusive practices for individual transgender students to resist further structural changes to cisnormative systems. Staley and Leonardi (2020) propose the overarching approach to content learning needs to shift towards conversations of oppression, power, and the self with a greater focus on active learning that prepares teachers to “disrupt normativity.” Preparing teachers to disrupt normativity includes providing active learning opportunities. Rather than passively listening to a lecture on gender and sexuality in schools, active learning involves opportunities for reflection and to practice changing instruction, discipline, and social interactions.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Still, a number of IPD evaluations suggest investing resources into intensive IPD with collective participation, duration, coherence, active learning, and content learning could lead to improved school climates. Staley and Leonardi (2020) stressed the importance of IPD with a queer pedological lens that has the potential to disrupt broader systems of oppression in schools. While acknowledging the challenges to sustaining the political and financial resources for this kind of IPD training, they highlight the need to provide resources and space for continuous reflection – both for educators and those delivering IPD to diverse school contexts.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of institutional resources needed to effectively learn about policies concerning gender helps explain why leaders have resisted implementing policy mandates concerning transgender students in New York (Payne & Smith, 2018; Woolley, 2019) and California (Leonardi, 2017), while other leaders have been primed with a trans-informed approach through their experiences with transgender students (Mangin, 2019), transgender educators, or gender-inclusivity professional development (Smith & Payne, 2016; Staley & Leonardi, 2020). Researchers examining motivated reasoners and bias suggest most individuals have an affective tipping point (Redlawsk, Civettini, & Emmerson, 2010).…”
Section: Conceptual Framework: Administrators’ Sensemaking and Hot Co...mentioning
confidence: 99%
“…Queer theory, when it meets pedagogy, considers what knowledge does to students (Britzman, 1998;Kumashiro, 2000;Luhmann, 1998). When it comes to learning about gender and sexual diversity and LGBTQ+ identities, for many students, this is "difficult knowledge" (Britzman, 1998(Britzman, , 2000Staley & Leonardi, 2020) and their learning processes are fraught with emotion, resistance, and moments of what Kumashiro (2000) calls crisis, wherein learners are challenged to rethink themselves, who they know themselves to be. Attending to the possibilities of what knowledge will do to students, how they might position themselves in conversations and in the content, is critical for educators to create favorable contexts of choice, as well as, to create contexts for learning (Britzman, 1998).…”
Section: Key Idea #2 In Practice: Queering Equal Educational Opportunities Autonomy and Recognition In Fairmentioning
confidence: 99%